Refractory Hepatic Hydrothorax: A Rare Complication of Systemic Sclerosis and Presinusoidal Portal Hypertension - Gary A. Abrams; Robert Chapman; Samuel R. W. Horton (Case Reports in Hepatology)
We report on a rare case of refractory hepatic hydrothorax in an individual with Scleroderma/CREST syndrome and noncirrhotic portal hypertension. Portal pressure measurements revealed a normal transjugular hepatic venous portal pressure gradient, mild pulmonary hypertension, and an unremarkable liver biopsy except for mild sinusoidal dilation. Pulmonary hypertension, cardiac diastolic dysfunction, and chronic kidney disease were determined to be the causes of his refractory pleural effusions and ascites. Over the year, he underwent 50 thoracenteses and 20 paracenteses averaging 10–12 liters/week. Repeat pulmonary evaluation determined his pulmonary pressures to be normal and a secondary review of the “unremarkable” liver biopsy noted mild venous outflow obstruction and possibly Nodular Regenerative Hyperplasia (NRH). Repeat portal pressures indirectly and directly confirmed the existence of presinusoidal portal hypertension that has been associated with NRH. A transjugular intrahepatic portal systemic shunt (TIPS) was placed and he has not required thoracentesis or paracentesis over the past 18 months.